1985
DOI: 10.1172/jci112090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dichloroacetate in the treatment of hypoxic lactic acidosis in dogs.

Abstract: The metabolic and systemic effects of dichloroacetate (DCA) In conclusion, DCA therapy in hypoxic lactic acidosis has beneficial systemic effects compared with therapy with NaCI. DCA administration is accompanied by increases of blood pH and bicarbonate, a decrease in lactate production, and enhanced liver lactate extraction, and a lowering of tissue lactate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 18 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Dichloroacetate (DCA)' has been used to lower the blood lactate concentration in humans and experimental animals with lactic acidosis (1)(2)(3)(4). This effect has been attributed to stimulation of pyruvate dehydrogenase activity, resulting in increased lactic acid oxidation (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloroacetate (DCA)' has been used to lower the blood lactate concentration in humans and experimental animals with lactic acidosis (1)(2)(3)(4). This effect has been attributed to stimulation of pyruvate dehydrogenase activity, resulting in increased lactic acid oxidation (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Graf et al. (3) measured muscle lactate concentration and hindlimb arteriovenous lactate differences in dogs with hypoxic lactic acidosis and concluded that DCA increased hepatic lactate extraction and reduced lactate production in skeletal muscle. This implies that DCA inhibits glycolysis in peripheral tissues, yet it was concluded that DCA did not reduce glycolysis in the rat hindquarter perfused without insulin (8).…”
Section: Introductionmentioning
confidence: 99%
“…So far, there is little direct evidence available to support the idea that dichloroacetate enhances muscle oxygen delivery. However, it has been shown that oxygen delivery to canine hypoxic skeletal muscle was enhanced following dichloroacetate infusion (Graf, Leach, & Arieff, 1985). Furthermore, when human volunteers were given the same amount of dichloroacetate to the present study (50…”
Section: Vomentioning
confidence: 66%
“…The precise mechanism(s) behind these effects are not clear, but it has been suggested (Graf et al 1985) that it could involve the binding of oxygen to haemoglobin. Whether this is related to an increase in haemoglobin oxygen saturation, an enhanced unloading of oxygen at the site of gas exchange or an interaction with nitric oxide release (reduced peripheral resistance and thus enhanced blood flow) is as yet unclear.…”
Section: Vomentioning
confidence: 99%
“…Oxalate, a metabolite of DCA, may be responsible for some of its in vitro Effects of Bicarbonate and Dichloroacetate in Experimental Phenformin-Induced and Hypoxic Lactic Acidosis pHi = intracellular pH. (Adapted from Graf et al [9], Arieff et al [19], Park et al [22], Park et al [38], Arieff et al [39], and Graf et al [44].) enzyme inhibition, whereas glyoxylate, another DCA metabolite, appears to be inactive [40].…”
Section: Treatmentmentioning
confidence: 99%